Pemanfaatan Media Sosial untuk Meningkatkan Omzet Usaha Jajan Bali Mahalaksmi Desa Petang - Ni Putu Nanik Hendayanti; Gusti Ayu Aghivirwiati; Deviana; Gusti Ayu Desi Saryanti; Gusti Ngurah Ady Kusuma; Rosalia Hadi; Maulida Nurhidayati (Amaluna: Jurnal Pengabdian Masyarakat, 2023)
The entrepreneurial effort of Bali Mahalaksmi snack production, owned by Mrs. I Dewa Ayu Sutari, is a household industry located in Banjar Petang, Petang Village, Petang District, Badung Regency. Mrs. Sutari has been engaged in the production of Balinese snacks for approximately two years. During this period, the production of Bali Mahalaksmi snacks for partners varies daily, depending on orders from small shops, stalls, neighbors, and relatives. This variability in orders results in inconsistent income for the partners. The customer base primarily consists of residents from the partner's village, with some from neighboring villages. Consequently, the marketing scope for Mrs. Sutari's snack business is limited. To address this marketing management challenge, a community partnership program was implemented, focusing on training in social media platforms such as Instagram and Facebook to broaden the partner's market reach. Asset Based Community Development (ABCD) method was employed for this engagement. The outcomes of the program include the establishment of Instagram and Facebook marketing channels for the partner, contributing to an increase in the partner's business turnover.